Angelina At the Fair - Holabird, Katharine (Middleton, WI, 2000)
Angelina's annoyance at having to take her little cousin Henry to the fair turns into friendship after a day filled with adventures and surprises.
"Ages 3 and up"--Jkt.
Keywords: Fairs; Fiction; Cousins; Fiction; Mice; Fiction